EVALUATION OF DEPRESSION FREQUENCY AND ITS EFFECT ON PROGNOSIS IN PATIENTS TREATED FOR ACUTE ISCHEMIC STROKE - Kalyoncu Aslan, Işıl; Akpinar, Ahmet; Salt, Irmak (PERDOSSI (Perhimpunan Dokter Spesialis Saraf Indonesia Cabang Malang) - Indonesian Neurological Association Branch of Malang cooperated with Neurology Residency Program, Faculty of Medicine Brawijaya University, Malang, Indonesia, 2024)
Background: Stroke is one of the most important causes of mortality and morbidity in the world. Although mortality and morbidity rates decrease with mechanical thrombectomy and intravenous thrombolytic treatments in suitable patients, post-stroke depression may develop in these patients. Poststroke depression occurs in approximately 30% of patients with stroke and is associated with poor prognosis and quality of life. Objective: Depression is a common complication that leads to dysfunction even years after a stroke. In this study, we aimed to evaluate the frequency of depression, determine the risk factors, the relationship between the infarct localization and stroke severity in patients who underwent acute ischemic stroke treatment (intravenous tissue plasminogen activator (IV-tPA) and/or endovascular mechanical thrombectomy (MT)). Methods: In this prospective study, 230 patients older than 18 years of age who were hospitalized with the diagnosis of acute ischemic stroke between 2021-2022 and treated for acute ischemic stroke were evaluated. Patient characteristics such as age, gender, education level, stroke risk factors, infarct localization were noted in the first month follow up outpatient clinic as well as their Modified Rankin Score (MRS), National Health Institutes Stroke Scale (NIHSS) and Beck Depression Scale (BDI). Results: There was a statistically significant difference in age groups compared to BDI values (x2=10.215, p=0.037). A statistically significant difference was found between BDI levels and MRS (x2=21.177, p<0.001) and BDI score and NIHSS (x2=28.074, p<0.001). There was a statistically significant difference between education levels and MRS values (x2=17.147, p=0.002) and NIHSS scores(x2=14.715, p=0.005). Conclusion: Whereas disability can lead to depression, depression is one of the leading causes of disability. Despite the benefit of acute stroke treatments, they are ineffective in preventing post-stroke depression and subsequent disability. Therefore identification, and prevention of risk factors and early treatment of depression are necessary to effectively prevent morbidity.